Frequency of Atrial Fibrillation in Acute Ischemic Stroke Patients at Tertiary Care Hospital - Muhammad Khalid, Muhammad Haroon Shahid, Muhammad Arif, Ghulam Jaffar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Stroke is defined as the abrupt development of a neurologic impairment caused by a vascular mechanism. Atrial fibrillation raises the risk of stroke by five times and is responsible for overall 15 to 20% cases of strokes. Objective: To find out the frequency of atrial fibrillation in acute ischemic stroke patients at tertiary care hospital Methodology: The current study was descriptive done at the Medicine Department Qazi Hussain Medical Complex, Nowshera for duration of six months from November 2021 to April 2022. A 12 lead ECG was carried out for all the patients to confirm the presence of Atrial Fibrillation. All the data was collected by using predesigned Performa. Data analysis was done by using IBM SPSS version 20. Results: In the current study, a total of 150 acute ischemic stroke patients were enrolled. There were 85 (56.67%) male and 65 (43.33%) females in our study. The overall frequency of atrial fibrillation was 18.67% (n=28). Based on the age wise distribution, atrial fibrillation was observed in 2 (7.14%) patients in age group ≤50 years, 4 (14.29%) in age group 51-60 years, 7 (25%) in 61-70 years, 13 (46.83%) in age group 71-80 years and 2(7.14%) in age group ˃80 years. Conclusion: In our study atrial fibrillation was observed in 18.67% patients with acute ischemic stroke. Majority of the patients were old and observed wit unknown atrial fibrillation. Atrial fibrillation should be monitored in patients with acute ischemic stroke.